PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (PERSPEKTIF AL-QUR’AN) - Herry, Musleh (ULUL ALBAB Jurnal Studi Islam, 2008)
Al-Qur'an and of Hadist represent guidance of public or made hold, according to Islam about levying of land for the sake of the public. In al qu'ran, expressed that Allah bestow big grant from above to human being by creating earth, natural resources and water which consist in in it to the human being to be used human being to be able to take care of the continuity of its life and so that human being devote to Allah of SWT, to family and to society. By its, land existence has to be utilized to its of prosperity of society as arranged in Section 33 sentence (3) UUD 1945.